2022
DOI: 10.3389/fphar.2022.873108
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin Attenuates Myocardial Fibrosis by Inhibiting the TGF-β1/Smad Signaling Pathway in a Normoglycemic Rabbit Model of Chronic Heart Failure

Abstract: Recent studies have shown that sodium-glucose cotransporter-2 (SGLT2) inhibitors play a beneficial role for normoglycemic patients with heart failure (HF). However, the underlying mechanism remains largely unexplored. In the present study, we aimed to investigate the cardioprotective effect of SGLT2 inhibitors in a normoglycemic rabbit model of chronic heart failure (CHF) and its potential mechanism was also explored. A total of 24 male New Zealand white rabbits were randomly divided into the sham group, HF gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Comparably, SMIT has been reported to be an important driver of acute myeloid leukemia cell 20 proliferation 61 and pharmacological inhibition with phlorizin, the substance DAPA and EMPA are derived from, led to reduced proliferation and migration of lung cancer cells 62 . Based on the described reduction in effect size of SGLT2is on HCF proliferation upon respective KD, we conclude that antifibrotic cardiovascular effects of SGLT2is [63][64][65] are mediated through their direct binding and inhibition of SMIT, SMVT, and NHE1.…”
Section: Discussionmentioning
confidence: 70%
“…Comparably, SMIT has been reported to be an important driver of acute myeloid leukemia cell 20 proliferation 61 and pharmacological inhibition with phlorizin, the substance DAPA and EMPA are derived from, led to reduced proliferation and migration of lung cancer cells 62 . Based on the described reduction in effect size of SGLT2is on HCF proliferation upon respective KD, we conclude that antifibrotic cardiovascular effects of SGLT2is [63][64][65] are mediated through their direct binding and inhibition of SMIT, SMVT, and NHE1.…”
Section: Discussionmentioning
confidence: 70%
“…Multiple studies in the past 2 decades show that dysregulated mTORC1 plays a critical role in the pathophysiology of kidney diseases, NAFLD, cardiovascular and neuronal disorders, and cancer ( 23 25 , 40 ). Fine-tuned, moderate inhibition of mTORC1 is beneficial in that it reduces the cellular workload and stimulates autophagy and mitophagy, which improve protein and organelle quality control, thereby reducing cellular stress and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in the past two decades showed that dysregulated mTORC1 plays a critical role in the pathophysiology of kidney diseases, NAFLD, cardiovascular and neuronal disorders as well as cancer (23)(24)(25)40).…”
Section: Implications Of Mtorc1 Inhibition For Diabetes Complications...mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, although there are clinical data showing that sodium-glucose cotransporter-2 inhibitors reduce BP 59 and LVM, 60,61 and experimental data showing their ability to attenuate MIF, 62 no evidence is still available on their effects on either PICP or ECV and on their effectiveness to reduce the risk of HF in HHD.…”
Section: Preventive and Therapeutic Aspectsmentioning
confidence: 99%